2021
DOI: 10.3390/s21165283
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diabetic Eye Disease from Retinal Images Using a Deep Learning Based CenterNet Model

Abstract: Diabetic retinopathy (DR) is an eye disease that alters the blood vessels of a person suffering from diabetes. Diabetic macular edema (DME) occurs when DR affects the macula, which causes fluid accumulation in the macula. Efficient screening systems require experts to manually analyze images to recognize diseases. However, due to the challenging nature of the screening method and lack of trained human resources, devising effective screening-oriented treatment is an expensive task. Automated systems are trying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 38 publications
(57 reference statements)
0
35
0
1
Order By: Relevance
“…While simply duplicating videos leads to algorithm performance failure due to overfitting, image augmentations such as rotation, inversions, contrast changes, and others can result in a more robust algorithm than would be possible otherwise with limited data. 38 Not only is the difference in anatomic appearance between the A4C and SX imaging windows inherently a challenge, but also simply using data from a different type of ultrasound machine can markedly decrease performance for algorithms. 39 Both were factors at play in the current research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While simply duplicating videos leads to algorithm performance failure due to overfitting, image augmentations such as rotation, inversions, contrast changes, and others can result in a more robust algorithm than would be possible otherwise with limited data. 38 Not only is the difference in anatomic appearance between the A4C and SX imaging windows inherently a challenge, but also simply using data from a different type of ultrasound machine can markedly decrease performance for algorithms. 39 Both were factors at play in the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Video rotations and flips allowed the researchers to convert a 191 video dataset into 3820 videos used for algorithm training. While simply duplicating videos leads to algorithm performance failure due to overfitting, image augmentations such as rotation, inversions, contrast changes, and others can result in a more robust algorithm than would be possible otherwise with limited data 38 …”
Section: Discussionmentioning
confidence: 99%
“…This study showed that pre-processing of data prior to model building enhances prediction accuracy ( 35 ). Machine learning methods are also used for the detection of some other medical diseases detection ( 36 38 ), text mining ( 39 42 ) and network security ( 43 47 ). Another analysis is conducted to predict the risks associated with diabetes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The DCNN model achieved an accuracy of 91.2%, specificity of 94.4%, and sensitivity of 87.5%. A custom deep learning-based CenterNet model was developed by Nazir et al [36] for various DR lesions' classification. Their method involved dataset preparation and feature extraction using DenseNet-100.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In horizontal reflection, all image columns are flipped around the vertical axis, as shown in Figure 4. Training a deep learning model with an augmented dataset has been shown to improve the performance of the model, reduce overfitting, and increase the model's ability to generalize [36]. In order to balance the augmented dataset, the same number of images for each class was used, providing a total number of 888 images.…”
Section: Original V Channel Enhanced V Channelmentioning
confidence: 99%